Impact of trade liberalisation on poverty in Zimbabwe (1986-2012) - Musvovi, George (Midlands State University, 2017)
Since the late 1980s, Zimbabwe has experienced rising poverty for quite a number of years despite policy makers implementing trade liberalisation. Therefore, the study sought to determine the impact of trade liberalisation on poverty in Zimbabwe. Using time series data from 1986 to 2012, an Ordinary Least Squares (OLS) estimation criteria was employed to estimate the change of poverty in Zimbabwe. The study found out that trade liberalization has positive effect on poverty. Policy makers need to be cautious when introducing such a policy. The research recommends complementary policies that ensure benefits of trade liberalization are maximized while losses are minimized.